Перші відомості про дискоміцети Дунайського біосферного заповідника - Дудка, І.О.; Зикова, М.О. (Український ботанічний журнал, 2010)
В октябре 2009 г. проведено микологическое обследование разных типов растительных сообществ Дунайского биосферного заповедника НАН Украины, в результате которого выявлено 16 видов дискомицетов из классов Leotiomycetes, Lecanoromycetes и Orbiliomycetes. Наибольшим числом видов представлен порядок Helotiales (13), а среди родов — Hymenoscyphus Gray (4). Приведены краткие диагнозы и рисунки трех новых для Украины видов — Rutstroemia lindaviana (Kirschst.) Dennis, Perrotia distincta (Peck) J.H. Haines и Cryptodiscus tabularum Kirschst. During a mycological expedition to Danube Biosphere Reserve in October 2009, 16 species of discomycetes from the classes Leotiomycetes, Lecanoromycetes and Orbiliomycetes were recorded in different types of vegetation. The highest species diversity was observed in the order Helotiales (13) and in the genus Hymenoscyphus Gray (4). Brief descriptions and drawings of Rutstroemia lindaviana (Kirschst.) Dennis, Perrotia distincta (Peck) J.H. Haines, and Cryptodiscus tabularum Kirschst., new species for Ukraine, are given.